2007
DOI: 10.1248/yakushi.127.1757
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel Oxadiazole and Oxadiazoline Analogues for Their Antiinflammatory Activity

Abstract: The search for newer non-steroidal antiin‰ammatory drugs (NSAIDs) and the importance of oxadiazoles as antiin‰ammatory agents prompted us to undertake the synthesis of some novel oxadiazole and related analogues with unreported antiin‰ammatory activities. The antiin‰ammatory potential of the compounds was investigated using the carrageenan-induced rat paw edema method and cotton pellet-induced granuloma method. Some compounds demonstrated marked antiin‰ammatory activities. The antiin‰ammatory activity of oxadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…Substituted aryl semicarbazones (2) were prepared according to the method reported in the literature using semicarbazide hydrochloride and substituted aldehydes in alcohol (Furniss et al, 2005a, b). 2-Amino-5-aryl-1,3,4-oxadiazoles (3) were prepared by cyclization of semicarbazones of the corresponding aromatic aldehydes in the presence of bromine in glacial acetic acid (Rajak et al, 2007). N-benzoyl anthranilic acid (5) was prepared by reaction of anthranilic acid with benzoyl chloride.…”
Section: Chemistrymentioning
confidence: 99%
“…Substituted aryl semicarbazones (2) were prepared according to the method reported in the literature using semicarbazide hydrochloride and substituted aldehydes in alcohol (Furniss et al, 2005a, b). 2-Amino-5-aryl-1,3,4-oxadiazoles (3) were prepared by cyclization of semicarbazones of the corresponding aromatic aldehydes in the presence of bromine in glacial acetic acid (Rajak et al, 2007). N-benzoyl anthranilic acid (5) was prepared by reaction of anthranilic acid with benzoyl chloride.…”
Section: Chemistrymentioning
confidence: 99%
“…Substituted aryl semicarbazones were prepared according to the method reported in the literature using semicarbazide hydrochloride and substituted aldehydes in alcohol (Furniss et al, 2005a). 2-Amino-5-aryl-1,3,4-oxadiazoles (1) were prepared by cyclization of semicarbazones of the corresponding aromatic aldehydes in the presence of bromine in glacial acetic acid (Rajak et al, 2007). Substituted oxadiazole amines (1) were treated with sodium cyanate in the presence of glacial acetic acid according to the known urea method to yield substituted phenyl urea derivatives (2) (Furniss et al, 2005b).…”
Section: Chemistrymentioning
confidence: 99%
“…Recently, 1,3,4-oxadiazoles derivatives exhibited broad spectrum of biological activates likewise antitumor 16 ,antiproliferative 17 , a-glucosidase inhibitors 18 ,anti-inflammatory [19][20][21] ,antibacterial 22 , antifungals 23,24 as well the antioxidant ability [25][26][27] . Many researchers have reported that the substituent group at ortho of phenols possess directly control to improve or disprove the antioxidant capacity [28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%